Modern transformation processes in the settlement system of the Zaporizhia region as a result of the reform of the administrative-territorial structure - Kobets, Kseniia (Human Geography Journal, 2021)
Reforming the administrative-territorial structure on the basis of union village and urban councils into territorial communities has led to new transformation processes in the settlement system of Zaporizhia region and the country as a whole. The article analyzes the union of territorial communities in Zaporizhia region after the completion of the decentralization reform, calculates the density of population, settlements and the average quantity of settlements in territorial communities in the districts of Zaporizhia region.The study region ranks fifth in Ukraine among of united territorial communities. Almost 65% of the total population of the region is concentrated in Zaporizhia, Melitopol, Berdyansk, Energodar and Tokmak urban territorial communities. In the course of the research it was determined that more than a third of all communities of Zaporizhia region have a population of 5 to 10 thousand people. In the region is dominated by communities with an area of 100-200 km2 and 200-300 km2. Chernihivska, Yakymivska and Primorska united territorial communities were created without taking into account the availability of public services for all settlements of the community.The highest population density is observed in the north-west of Zaporizhia region and in points in the united territorial communities, which include large cities in the region. In two thirds of the territorial communities of the region the amount of settlements does not exceed 15. Territorially, the highest density of settlements is observed in the north of Zaporizhia region, and the lowest - in the south-east and west. During the calculation of the population concentration index, it was determined that in Vasylivka and Pologi districts there is an uneven distribution of the population. Zaporizhia, Melitopol, and Berdyansk districts stand out with their abruptly uneven distribution of population.As a result of the change of the administrative-territorial structure of the Zaporizhia region, the process of functional transformation of the settlement system began. The Chernihivska, Yakymivska, Huliaipilska and Primorska communities have merged a large amount of local councils, so they will be most affected by changes in the functional connections between the settlements. There was also a breaking in functional connections in the settlements that were separated from the main part of the territory of the former districts.